Menemukan Nilai-Nilai Kebermaknaan Hidup Melalui Profesi Guru Bimbingan dan Konseling - Nining Mulyaningsih (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
ABSTRACTThe implementation of quality and effective education is to integrate the three components of the education system which include management and leadership components, educational learning components, and independent guidance and counseling components. In the midst of government attention getting better at strengthening the existence of guidance and counseling in educational institutions, the implementation of guidance and counseling activities in schools is a challenge for guidance and counseling teachers with a lack of support from management and leadership as well as paradigms in the eyes of students and the community. Then how do guidance and counseling teachers face these challenges and obstacles in meeting the demands of the task as one of the important components in the implementation of education. This study aims to find out what the background of guidance and counseling teachers can work as well as possible amid the challenges and obstacles faced by both colleagues, students and the leadership and management. The research method uses a qualitative approach to the type of phenomenology. Data collection techniques through interviews. The participants consisted of three guidance and counseling teachers with 6 years, 11 years and 27 years of service. The results showed that the three participants had values ​​in achieving the meaning of life. Either through Creative values, Experiential Values ​​and Attitudinal Values Keywords: Counseling Guidance Teacher, Meaning of Life